GAHS TAHP: the glasgow alcoholic hepatitis score in the treatment of alcoholic hepatitis in practice. (13th March 2011) - Lafferty, H; Watson, E; Hamid, R; Winter, J; Morris, J; Stanley, A; Forrest, E
Abstract : Introduction: Alcoholic hepatitis (AH) continues to be a frequent cause of alcohol related mortality. The Glasgow Alcoholic Hepatitis Score (GAHS) has not only been proposed as an accurate measure of prognosis, but also as a guide to therapeutic intervention. However these studies have been retrospective. The authors assessed the use of the GAHS in the management of unselected patients with AH. Methods: 182 patients with a clinical diagnosis of AH were assessed prospectively (Group 1), and then compared with a historical control group (Group 2). All patients had an admission serum bilirubin greater than 80 μmol/l. No patients were Hepatitis C PCR positive or had presented with evidence of upper gastro-intestinal haemorrhage. The unit protocol was for treatment with prednisolone 40 mg or pentoxifylline 400 mg three times a day at the discretion of the responsible consultant when the GAHS was ≥9 in Group 1. No Group 2 patients received either prednisolone or pentoxifylline (Group 2). Results: Overall 28-day survival figures for Group 1 and Group 2 were 150 (82.4%) and 129 (73.7%) respectively (p=0.03; HR 1.64 (1.06–2.56)). The respective 84-day survival rates were 126 (69.2%) and 119 (68%) (p=0.41; HR 1.17 0.806–1.70)). In Group 1, 96 patients developed a GAHS ≥9 during the first week of their hospital admission (58%). On comparison Group 1 and 2 patients with a GAHS<9 had similar rates of survival at day 28 and 84. However differences were seen between patients with a GAHS ≥9. At 28 days the survival rates of Group 1 and Group 2 were 71% and 41% respectively (p=0.0002; HR 2.86 (1.64–3.18)). At 84 days the survival rates of the Group 1 and Group 2 were 54% and 37% respectively (p=0.008; HR 1.95 (1.19–3.18)). The improvement in outcome was more clearly seen in GAHS ≥9 patients who received treatment as per protocol (80 of 96: 83%). Reasons given for not receiving treatment were as follows: 10 suspected sepsis (confirmed: 3 SBP; 3 chest sepsis; 1 secondary peritonitis), 1 upper gastro-intestinal haemorrhage after admission and 1 patient's condition deteriorated too rapidly to allow treatment to start. In 4 cases no reasons were given. Conclusion: The GAHS can be used in clinical practice. A GAHS ≥9 identifies patients who may benefit from treatment.